Degrees of cross-polarization of a partially coherent electromagnetic beam in uniaxial crystals - Li, Jia; Chen, Yanru; Zhao, Qi; Zhou, Muchun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Propagation of degrees of cross-polarization of a partially coherent electromagnetic beam in uniaxial crystals orthogonal to the optical axis is investigated. Based on the paraxial theory of beams, analytical propagation formulas for degrees of cross-polarization are derived and analyses are illustrated by numerical examples. It is found that values of the degree of cross-polarization in uniaxial crystals fluctuate more rapidly with larger deviation of correlation length parameters (δij – δii), but show slight variation with larger ratio of refractive index (ne/n0) or incident beam wavelength. Results also show that sources with sufficient correlation length parameters generate invariable degree of cross-polarization in uniaxial crystals.
Optica Applicata, Vol. 40, 2010, nr 1, s. 93-100
Keywords: optyka; cross-polarization; uniaxial crystal; correlation length; refractive index